OGBN O01 Laparoscopic large hiatus hernia repair with mesh versus suture: a systematic review and meta-analysis. (7th December 2022) - Rajkomar, Kheman; Wong, Michael; Gall, Lewis; MacKay, Colin; MacDonald, Andrew; Forshaw, Matthew; Craig, Carol
Abstract: Background: Whilst the use of laparoscopy in the repair of large hiatus hernia (LHH) has become mainstream, the prevention of post operative hernia recurrence and other adverse events has remained a challenge. Mesh reinforcement of suture cruroplasty has been considered as a potential solution. However the paucity of well constructed and powered randomised control trials (RCT) with long term followup makes an assessment of its real impact difficult. The aim of this review is to evaluate the effectiveness of mesh reinforcement of LHH repair, with regards to postoperative outcomes. Methods: A systematic search of articles was conducted in PubMed, Medline and Embase using the PRISMA guidelines. RCTs and observational studies (OS) comparing recurrences and reoperations in those patients with LHH (>30% stomach in chest, >5cm hiatal defect, hiatal surface area >10 mm 2 ) repair who had mesh vs no mesh were assessed quantitatively. The impact of mesh on significant intraoperative/postoperative surgical complications and mortality were qualitatively assessed. Results: Pooled data included five RCTs and fourteen OS with 1670 patients (824 with no mesh, 846 with mesh). There was a significant reduction in total recurrence rate with mesh (OR 0.44, 95% CI 0.25 to 0.80, p = 0.007). Mesh use did not cause significant reduction in recurrences >2cm (OR 0.94, 95% CI 0.52 to 1.67, p = 0.83) or significant reduction in reoperation rates (OR 0.64, 95% CI 0.39 to 1.07, p = 0.09). None of the meshes were found to significantly reduce recurrence or reoperation rate on subgroup analysis, although the number of studies using a single mesh type was limited. Major morbidity rates associated with LHH repair included mesh erosion with foregut resection (from synthetic mesh) and esophageal perforation and were 0.71% and 0.36% respectively. An overall mortality rate of 0.3% was found in the pooled patients. Conclusions: Mesh reinforcement in LHH is protective against total recurrence. However there is no significant reduction in large recurrences (>2cm) or reoperation rate. If synthetic mesh is to be used patients need to be informed of the risk of mesh erosion.